2013
DOI: 10.1186/1475-2840-12-112
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the LDL subfraction phenotype on Lp-PLA2 distribution, LDL modification and HDL composition in type 2 diabetes

Abstract: BackgroundQualitative alterations of lipoproteins underlie the high incidence of atherosclerosis in diabetes. The objective of this study was to assess the impact of low-density lipoprotein (LDL) subfraction phenotype on the qualitative characteristics of LDL and high-density lipoprotein (HDL) in patients with type 2 diabetes.MethodsOne hundred twenty two patients with type 2 diabetes in poor glycemic control and 54 healthy subjects were included in the study. Patients were classified according to their LDL su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 35 publications
3
35
0
Order By: Relevance
“…Gazi et al found that plasma Lp-PLA 2 activity was a marker of sdLDL due to the preferential distribution of Lp-PLA 2 in the sdLDL subfraction in patients with dyslipidemia [15]. A recent study demonstrated that the presence of LDL subfraction phenotype B (the predominance of sdLDL) was associated with an increased Lp-PLA 2 activity in patients with type 2 diabetes as well as with abnormal HDL composition [16]. Although both dyslipidemia and diabetes reflected high risk of cardiovascular disease, the pathophysiology of CAD was a more complicated process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gazi et al found that plasma Lp-PLA 2 activity was a marker of sdLDL due to the preferential distribution of Lp-PLA 2 in the sdLDL subfraction in patients with dyslipidemia [15]. A recent study demonstrated that the presence of LDL subfraction phenotype B (the predominance of sdLDL) was associated with an increased Lp-PLA 2 activity in patients with type 2 diabetes as well as with abnormal HDL composition [16]. Although both dyslipidemia and diabetes reflected high risk of cardiovascular disease, the pathophysiology of CAD was a more complicated process.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, understanding the relationship between lipoprotein subfractions and Lp-PLA 2 may provide more evidence regarding the potential risk of Lp-PLA 2 for CAD. Previous data have reported the association between plasma Lp-PLA 2 activity and small dense LDL (sdLDL) in patients with dyslipidemia [15] or type 2 diabetes [16]. However, to the extent of our knowledge, the relationship between lipoprotein subfractions and Lp-PLA 2 has not been revealed in the status of CAD.…”
Section: Introductionmentioning
confidence: 86%
“…According to this assumption, Lp-PLA 2 is anti-inflammatory when bound to HDL, but pro-inflammatory when bound to LDL [19]. Moreover, an increase in the binding between Lp-PLA 2 and LDL was observed in diabetic patients [20], which could support the pro-atherosclerotic role of Lp-PLA 2 in diabetes. However, studies on sPLA 2 in diabetic patients are lacking in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Because of this, some researcher raised a hypothesis that when linked to LDL, Lp-PLA 2 would be pro-atherogenic, whereas its action in the HDL particle would be anti--atherogenic (39). Other researchers observed that the greater the LDL/Lp-PLA 2 and HDL/Lp-PLA 2 ratio, the greater the levels of LDL-C, TG, glucose, insulin, and lower the levels of HDL-C in individuals with polycystic ovary syndrome (40).…”
Section: Emerging Cardiovascular Risk Markers Associated To Lipid Metmentioning
confidence: 99%